Answer:
The missing coefficient of the x-term of the given expression [tex](-x-5)^2=x^2+10x+25[/tex] after simplified is 10
Step-by-step explanation:
Given expression is [tex](-x-5)^2[/tex]
To find the missing coefficient of the x-term of the given expression as below:
First Solve the given expression :
[tex](-x-5)^2[/tex] which is in the form of [tex](x-y)^2=x^2-2xy+y^2[/tex]
Here x=-x and y=5
[tex](-x-5)^2=(-x)^2-2(-x)(5)+(5)^2[/tex]
[tex]=x^2+10x+25[/tex]
Therefore [tex](-x-5)^2=x^2+10x+25[/tex]
The missing coefficient of the x-term of the given expression [tex](-x-5)^2=x^2+10x+25[/tex] after simplified is 10